(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
This scientific article explores the web positioning optimization of Rotanuncio - Graphic Solutions in Manta, Ecuador, through strategies driven by Artificial Intelligence (AI). AI, as a groundbreaking technology, could enhance traditional SEO strategies, being key to visibility and ranking in search engines. The research encompasses literature review, specialist interviews, and case analysis, delving into the intersection between AI and SEO optimization. This study can contribute to specialists and entrepreneurs, serving as a foundation for future research on a topic with limited information.